The Dynamic Change of Immune Responses Between Acute and Recurrence Stages of Rodent Malaria Infection - Chen, Suilin; Gao, Yuanli; Fan, Yongling; Guo, Shuai; Zhou, Jian; Liu, Taiping; Xu, Wenyue (Frontiers in Microbiology, 2022)
Malaria infections are persistent as frequent recrudescence of the disease may occur following the acute infection stage, but the different immune responses that control the acute and recrudescence stages are still largely unknown. Using single-cell RNA sequencing (scRNA-seq), we showed that the number of Th1 and plasma cells in the spleen was significantly reduced during the recurrence stage compared to the acute stage of Plasmodium chabaudi chabaudi AS (P. chabaudi) infection. Additionally, the ability of both CD4+ T cell responses and B cells to control P. chabaudi recurrence was significantly reduced compared to their roles in the control of acute infection. In contrast, the number of innate immune cells, including red pulp macrophages (RPMs), gamma delta (γδ) T cells, and Dendritic cells (DCs) were significantly increased during the recurrence stage and showed to be critical for P. chabaudi infection recurrence control. Thus, our data strongly suggest the complementary role of innate immune responses in controlling malaria recrudescence when adaptive immune responses are suppressed. These findings shed new light on the development of immune interventions against malaria.